2021
DOI: 10.2337/dbi20-0028
|View full text |Cite
|
Sign up to set email alerts
|

A Journey in Diabetes: From Clinical Physiology to Novel Therapeutics: The 2020 Banting Medal for Scientific Achievement Lecture

Abstract: Insulin resistance and β-cell dysfunction are the core pathophysiological mechanisms of all hyperglycemic syndromes. Advances in in vivo investigative techniques have made it possible to quantify insulin resistance in multiple sites (skeletal and myocardial muscle, subcutaneous and visceral fat depots, liver, kidney, vascular tissues, brain and intestine), to clarify its consequences for tissue substrate selection, and to establish its relation to tissue perfusion. Physiological modeling of β-cell function has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Further support comes from recent adult data. The protective effect of female sex on CV health is lost in presence of additional comorbidities and stresses (such as type 2 diabetes, hypertension, hypercholesterinaemia, sedentary lifestyle, mental stress) [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further support comes from recent adult data. The protective effect of female sex on CV health is lost in presence of additional comorbidities and stresses (such as type 2 diabetes, hypertension, hypercholesterinaemia, sedentary lifestyle, mental stress) [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma insulin concentration after the insulin infusion initially (from 25 min until about 60 min) tended to be slightly greater in the AA group than in the NHW group and was not different between the two groups afterward (Figure 3F). Hepatic insulin delivery was greater in the AA group than in the NHW group during the first 10 minutes of the IVGTT (35 [8] vs. 21 [2] nmol, p < 0.05) and was not different between the two groups after the insulin infusion (Figure 3G). Plasma insulin clearance during the first 10 minutes after intravenous glucose injection (Figure 3E) and during the entire 120-minute IVGTT (not shown) was markedly lower in the AA group than in the NHW group.…”
Section: Postprandial Insulin Kinetics (Ogtt)mentioning
confidence: 98%
“…Insulin resistance and hyperinsulinemia are major independent risk factors for developing type 2 diabetes in people with obesity (1‐3). It has been proposed that African American (AA), compared with non‐Hispanic White (NHW), men and women with obesity have an increased risk for developing type 2 diabetes because they are more insulin resistant and because they have both an increased β‐cell response to glucose and markedly (~50%) impaired hepatic insulin clearance (4‐7).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies on fibroblasts demonstrated that the ability of insulin to bind, internalize, and regulate its own receptor is not altered in T2D [ 133 ]. This is not unexpected because T2D is primarily due to severe β-cell dysfunction whereas insulin sensitivity is no worse than in people with obesity without T2D [ 1 , 3 ].…”
Section: Effects Of Obesity and Type 2 Diabetes On Insulin Clearancementioning
confidence: 99%
“…Compared with healthy lean people, people with obesity have increased basal and postprandial plasma insulin concentrations [ 1 , 2 , 3 ]. People with obesity and type 2 diabetes (T2D) have lower postprandial insulin than those without T2D, and the relative insulin insufficiency is responsible for the marked hyperglycemia in people with T2D [ 1 , 2 , 3 ]. The prevailing thought is that the increase in plasma insulin in people with obesity is a compensatory response to obesity-associated insulin resistance.…”
Section: Introductionmentioning
confidence: 99%